In vitro studies on the antimicrobial, antioxidant and antidiabetic potential of Cephalaria gigantea - Mbhele, Nobuhle; Balogun, Fatai O.; Kazeem, Mutiu I.; Ashafa, Tom (Bangladesh Journal of Pharmacology, 2015)
This study evaluates the antimicrobial, antioxidant and antidiabetic potential of leaf and root extracts of Cephalaria gigantea. The results showed that the extracts inhibited both bacteria and fungi tested at MIC values which ranged from 3.1 to 12.5 mg/mL. The root water and leaf hydro-ethanol extracts had the highest content of phenolics exhibiting IC50 values of 310.9 mg/g and 275.2 mg/g respectively. The leaf water extract possessed the highest amount of flavonoids with IC50 value of 145.4 mg/g followed by root hydro-ethanol extract with IC50 value of 53.4 mg/g. The leaf and root water extracts had the best DPPH radical scavenging activity with IC50 values of 0.6 µg/mL and 2.8 µg/mL compared to gallic acid at 14.0 µg/mL. The leaf hydro-ethanol and root water extracts scavenged ABTS radical best. Also the leaf and root hydro-ethanol extract exhibited the best reducing power activity when compared to gallic acid. The root water and leaf ethanol extracts displayed the most potent inhibition of ?-amylase and ?-glucosidase respectively. It can be concluded that C. gigantea extracts possessed antioxidant and antidiabetic potentials but has poor antimicrobial activities.